Performance docente na (co)autoria de recursos educacionais abertos (REA) no ensino superior: atos éticos e estéticos - Jacques, Juliana Sales (2017)
The Open Educational Resources (OER) are ethical and aesthetic compositions that underpin open education by democratizing access to knowledge, consider the plurality of educational ideas and contexts through (co)authorship and open network sharing. The focus of this thesis is this opening movement, through the implementation of OER, aiming to overcome the naive conscience. The formation of the critical awareness of the subjects problematizes the distortions of copyright culture in educational contexts, constituting them in social (co)authors. Based on that, the problem of this research was: to what extent the teacher performance, in the (co) authorship of OER in Higher Education, potentiates ethical and aesthetic acts? Therefore, the cyclical spiral movement of action research sustained (re)planning, action, observation and reflection of the teaching performance for theoretical understanding, political and ideological of the OER movement and the (co)authoring of open compositions, in initial professor training courses, of the Education Center (EC) of the Federal University of Santa Maria (UFSM). The coupling theory and practice, powered by action research, have, in Bakhtinian dialogism and Freirean liberation education, the theoretical-methodological bases for the movements of the teaser. Thus, we elaborate different meanings in the dialogical analysis of the data produced: verbal utterances (observation registers and questionnaires) and verb-visual utterances (OERs performed). Our results lead us to the understanding that the teaching performance, when it enhances the legal opening of the compositions, constitutes as a first step of awareness and confrontation of the dominant culture (the copyright). Given this, we consider that confronting it presupposes a permanent search for freedom, through our critical insertion into reality. That is, it requires an understanding of the contradictions of this culture and of our condition as social (co)authors which, in ethical and aesthetic acts, we can transform reality by creating and strengthening the OER culture. Therefore, the teaching performance potentiates ethical and aesthetic actions in the (co)authorship of OER when it promotes the overcoming of naive consciousness and strengthens the formation of critical awareness.